PERBANDINGAN SENAM TERA DAN SENAM PROLANIS TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI - Elvianda, Vriska; Mulfianda, Riyan; Desreza, Nanda (Coping: Community of Publishing in Nursing, 2024)
Every year, the number of hypertension patients in Indonesia continues to rise. One of the causes of hypertension is a lack of physical activity such as exercise. This study aims to compare the effects of two types of exercises, namely tera exercise and prolanis exercise, on reducing blood pressure in hypertension patients. This quasi-experimen study used a two-group pretest-posttest design with a double pretest. The sample consisted of 60 hypertension patients selected using purposive sampling technique. The intervention involved performing tera exercise and prolanis exercise, each conducted 6 times over 3 weeks. Data analysis using paired T-test showed that both exercises were effective in reducing blood pressure, with p-values of 0.000 for tera exercise and prolanis exercise, respectively. Statistical analysis also indicated a significant difference between the two types of exercises in reducing blood pressure in elderly hypertension patients, with p-values of 0.025 and 0.032, respectively. Therefore, it can be concluded that there is a difference in the effect of reducing blood pressure between tera exercise and prolanis exercise.